2020
DOI: 10.3390/polym12020323
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Molecular-Weight-Polyethylene (UHMWPE) as a Promising Polymer Material for Biomedical Applications: A Concise Review

Abstract: Ultra-High Molecular Weight Polyethylene (UHMWPE) is used in biomedical applications due to its high wear-resistance, ductility, and biocompatibility. A great deal of research in recent decades has focused on further improving its mechanical and tribological performances in order to provide durable implants in patients. Several methods, including irradiation, surface modifications, and reinforcements have been employed to improve the tribological and mechanical performance of UHMWPE. The effect of these modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 184 publications
(201 reference statements)
2
89
0
Order By: Relevance
“…One of the case material couple simulated using Ansys software is CoCr alloy and Ti6Al4V for cup and femoral head component, respectively. However, the concern of (Anderson et al, 2004;Pulgarin and Albano, 2015) 380,000 0.26 500-1,700 2 CoCr (Al Jabbari, 2014;Puccio and Mattei, 2015) 230,000 0.3 280-380 3 SS316L (Yildiz et al, 2011;Naik et al, 2020) 200,000 0.3 190 4 UHMWPE (Puccio and Mattei, 2015;Hussain et al, 2020) 1,000 0.4 4-6 this research is not in MoM materials, where it investigated mixed material couples. The last conclusion showed that least wear when using the CoCr alloy on the ultra-high molecular weight polyethylene (UHMWPE) material.…”
Section: Introductionmentioning
confidence: 97%
“…One of the case material couple simulated using Ansys software is CoCr alloy and Ti6Al4V for cup and femoral head component, respectively. However, the concern of (Anderson et al, 2004;Pulgarin and Albano, 2015) 380,000 0.26 500-1,700 2 CoCr (Al Jabbari, 2014;Puccio and Mattei, 2015) 230,000 0.3 280-380 3 SS316L (Yildiz et al, 2011;Naik et al, 2020) 200,000 0.3 190 4 UHMWPE (Puccio and Mattei, 2015;Hussain et al, 2020) 1,000 0.4 4-6 this research is not in MoM materials, where it investigated mixed material couples. The last conclusion showed that least wear when using the CoCr alloy on the ultra-high molecular weight polyethylene (UHMWPE) material.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, it also has the highest impact resistance among all the polymers, which makes it an excellent candidate for biomedical applications. Numerous attempts have been made to use pristine UHMWPE or UHMWPE composites in the bulk form in biomedical applications [ 77 ]. However, there are very few studies where efforts have been made to explore the feasibility of using UHMWPE in the form of coatings in biomedical applications.…”
Section: Uhmwpe Coatings For Different Applicationsmentioning
confidence: 99%
“…Hydrogels based on polysaccharides and their hybrids show great promise for wound healing and cartilage regeneration [2]. Due to its low friction, high wear resistance, toughness, durability, ductility and biocompatibility, an ultra-high molecular weight polyethylene (UHMWPE) has found its way into numerous biomedical applications both in its bulk form, and in the form of coatings [3][4][5], especially as implants (total hip arthroplasty, joint implants, bone tissue engineering). Porous UHMWPE with high osteogenous properties has been successfully used to simulate cancellous-bone tissue [6].…”
Section: Introduction 1polymeric Materials For Biomedical Applicatiomentioning
confidence: 99%